Dynamic response of a gothic cathedral in Cyprus - Çaǧnan, Zehra; Chrysostomou, Christis; Kyriakides, Nicholas; Votsis, Renos (My University, 2015)
Within the scope of this study, dynamic response of the St. Nicholas Cathedral in Cyprus that dates back to the 13th century was assessed based on obtained earthquake records. This structure resembles to the Rheims Cathedral of France with a nave of seven bays ending in a polygonal apse, together with flanking aisles ending in apsidal chapels of similar shape. According to historical records, it sustained heavy earthquake damage twice to its roof structure and flying buttresses. The main construction material used at this structure is calcarenite. Back in 2011, a strong-motion network was installed at the cathedral, which recorded a series of small to moderate magnitude events since then. This strong motion network consisting of 10 tri-axial accelerometers is the only active structural health monitoring system in Cyprus. In this article, the time-domain and frequency-domain analysis of this data is presented.
Keywords: Historical structure; Seismic assessment; System identification; Unreinforced masonry structure